[Untitled item 10339/24698] - (:unkn) unknown (Forsyth County Public Library, 2009)
WSJ 7-22-56 p.B3.
Construction of W. A. Whitaker Elementary School, 1956. The school is located on Buena Vista Road, near Woodbine Road.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth